Correction: Thepthanee et al. Shrimp Lipids Inhibit Migration, EpithelialMesenchymal Transition, and Cancer Stem Cells via Akt/mTOR/c-Myc Pathway Suppression. Biomedicines 2024, 12, 722 - Chorpaka Thepthanee; Zin Zin Ei; Soottawat Benjakul; Hongbin Zou; Korrakod Petsri; Bhurichaya Innets; Pithi Chanvorachote (My University, 2024)
[...].
Keywords: Fatty Acid Research and Health